Spelling book about sexual and reproductive health for deaf such as emancipated technology: reflexive analysis - Sousa, Rosiléa Alves de; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2001)
This study treats of the analysis of a book about sexual and reproductive health for deaf. The books was tested by educational groups with the deaf. The self-confidence, the informality of the discussions and the evaluation of the book for the deaf showed us the emancipation of the group and the need of some corrections in this didactic material. Being supported by ideas of Nietsche (2000), we considered this material as an emancipated technology, for the fact of bringing this people, the opportunity to free of a subjection state, in what concerns to the knowledge in this area of health.